Crystal structures of the extracellular domain of LRP6 and its complex with DKK1 - Cheng, Zhihong (2011)
LRP5 and LRP6 are Wnt co-receptors essential for Wnt/β-catenin signaling. DKK1 inhibits Wnt signaling by interacting with the extracellular domain of LRP5/6, and is a drug target for multiple diseases. Here we present the crystal structures of the first and second halves of LRP6’s four propeller–EGF pairs (LRP6-E1E2 and LRP6-E3E4), and a LRP6-E3E4/DKK1 complex. Combined with EM analysis, these data demonstrate that LRP6-E1E2 and LRP6-E3E4 form two rigid structural blocks, with a short intervening hinge that restrains their relative orientation. DKK1c interacts with the top surface of the LRP6-E3 YWTD propeller, and likely also that of the LRP6-E1 propeller due to structural similarity, through conserved hydrophobic patches buttressed by a network of salt bridges and hydrogen bonds. Our work provides key insights for understanding LRP5/6 structure and the interaction of LRP5/6 with DKK, as well as for drug discovery.